The impact of office design on medically certified sickness absence - Morten Birkeland Nielsen; Stein Knardahl (Nordic Association of Occupational Safety and Health (NOROSH), 2020)
OBJECTIVE: The aim of this study was to determine the impact of three different office designs (cellular office, shared office, and open-plan workspace) on the risk of medically certified sickness absence and the number of days, respectively, of medically certified sickness absence over a 12-month follow-up period. METHODS: The study relied on a combination of self-report survey questionnaire data on office design supplemented with official registry data number of days with sickness absence from the Norwegian Labor and Welfare Administration. The sample comprised 6328 Norwegian office workers (57% women, age range: 19-70 years, mean age: 44 years). RESULTS: Adjusting for survey year, employees working in a shared office [risk ratios (RR) 1.18, 95% confidence interval (CI) 1.10-1.27] and an open-plan workspace (RR 1.12, 95% CI 1.02-1.22) had significantly higher risk of having had medically instances of certified sickness absence when compared to employees working in a cellular-office. Office design was not related to the number of days with absence. The associations were consistent across organizational affiliation, age, gender, whether the respondent had leadership responsibility, and educational level. CONCLUSION: The use of shared offices and open-plan workspaces is a risk factor for medically certified sickness absence. Providing employees with the opportunity to work in cellular offices may reduce absence rates.